Stress, Job Satisfaction, and Organizational Commitment Affect Turnover Intention at PT Berca Kawan Sejati Malang - Listiyana, Listiyana (LPPM Institut Studi Islam Sunan Doe, 2024)
Human capital stands as a pivotal corporate asset, executing premeditated actions crucial for realizing organizational objectives. Their efficacy forms a linchpin, determining triumph or decline. This study aims to decipher the impact of job-related stress and contentment on turnover inclination, a nexus possibly mediated directly or indirectly through organizational allegiance. Utilizing survey-based research, the study encompasses PT Berca Kawan Sejati's entire workforce, comprising 78 employees, employing a complete enumeration sample. Methodologically, the data analysis embraces Structural Equation Modeling (SEM) utilizing Smart PLS tools. Findings reveal that job stress notably triggers a positive and consequential turnover intention, while also negatively influencing organizational commitment. Conversely, job satisfaction's influence on turnover inclination lacks statistical significance. Interestingly, job satisfaction tangibly drives positive and significant organizational commitment. However, the interplay between job stress, job satisfaction, and turnover intention mediated by organizational commitment does not exhibit statistical significance. Ergo, organizational commitment inadequately mediates the interrelationship between job stress, job satisfaction, and turnover intention. In sum, this study underscores human resource's pivotal role, unveiling intricate dynamics encompassing job stress, job satisfaction, turnover intention, and organizational commitment.